Under the microscope: An experimental look at board transparency and director monitoring behavior. (30th January 2018) - Li, Weiwen; Krause, Ryan; Qin, Xin; Zhang, Junsheng; Zhu, Hang; Lin, Shanshan; Xu, Yuehua
Abstract : Research Summary: It is well known in corporate governance scholarship that independent directors differ in the vigilance with which they monitor corporate insiders. This difference depends largely on whether independent directors are concerned more with their public reputation or with their prospects in the director labor market. The explanation for this difference depends on an assumption of information asymmetry, however. In the present study, we relax the assumption of information asymmetry to examine how boardroom transparency affects directors' monitoring behavior. Using a randomized experimental study of actual independent directors, we find that boardroom transparency amplifies the effect of directors' inclinations toward either active or passive monitoring, with directors inclined toward vigilant monitoring becoming even more vigilant, and directors inclined toward passive monitoring becoming even more passive. Managerial Summary: In most advanced economies, the board's internal decision processes are either undisclosed or disclosed only to a very limited extent. It remains unknown, then, whether directors would behave differently if their behaviors were made public. We find that when their actions are disclosed to the public, directors concerned with their public reputations become more vigilant, whereas those concerned with their prospects for additional board seats become more passive in monitoring corporate insiders. Whereas regulatory bodies and corporate governance watchdogs have recently advocated for greater disclosure of the boardroom decision‐making process, our study suggests that such mandatory disclosure requirements can exacerbate, rather than alleviate, the problem of passive director monitoring.